Reproducible phantom for quality assurance in abdominal MRI focussing kidney imaging - Wolf, Marcos; Kommer, Stefan; Fembek, Sebastian; Dröszler, Uwe; Körner, Tito; Berg, Andreas; Schmid, Albrecht Ingo; Moser, Ewald; Meyerspeer, Martin (Frontiers in Physics, 2022)
Quality assurance (QA) in magnetic resonance imaging (MRI) requires test objects. ‘Phantoms’ provided by MR manufacturers are homogeneously filled spheres or cylinders, and commercially available products are often too small for abdominal imaging, particularly for enlarged polycystic kidneys. Here we present the design, manufacturing and testing of a dedicated, yet versatile, abdominal MRI phantom, that can be reproduced with relatively low costs. The phantom mimics a human abdomen in size and shape and comprises seven test fluids, representing various tissue types at 3 T. The conductivity and permittivity of the test fluids match the average abdomen and kidney with a relative permittivity (ε) 65 and 72 as well as conductivity 0.6 and 0.7 S/m, respectively. The T1 and T2 relaxation times cover healthy average abdomen and kidney tissue values (T1(abd): 856 ms and T1(kid): 1,106 ms; T2(abd): 52 ms and T2(kid): 67 ms), intermediate (T1: 1,183 ms and 1,271 ms; T2: 128 and 189 ms), and disease values for (polycystic) kidney (T1: 1,428 ms, 1,561 ms and 1763 ms; T2: 319 ms, 424 and 647 ms). T1 and T2 relaxation times were stable over 73 weeks. Our reasonably priced, durable and reproducible abdominal phantom enables single and multi-center QA for future collaborative studies aiming for various challenges around abdominal and, particularly, kidney imaging.